Microcirculatory depth of focus measurement shows reduction of tissue edema by albumin resuscitation in burn patients - Olcay Dilken; Annemieke Dijkstra; Göksel Güven; Bülent Ergin; Nicole Trommel; Margriet E. van Baar; Helma WC Hofland; Can Ince; Cornelis H. van der Vlies (Journal of Intensive Medicine)
Background: Severe burns induce volume shifts via capillary leaks, eventually requiring massive fluid resuscitation and promoting tissue edema. Albumin may help to mitigate the edema, thereby improving perfusion. This study shows that sublingual microcirculation measurements can quantify both tissue perfusion and edema. Methods: This prospective observational study was conducted between November 2018 and December 2019 in the intensive care unit of Maasstad Hospital Burn Center, Rotterdam, The Netherlands. Patients with severe burns affecting >15% of the total body surface area were included. Fluid management was conducted in accordance with the Parkland formula. Albumin (20%) was administered at a rate of 0.5 mL/(kg·h), starting 12 h after the burn incident. Alterations in the sublingual microcirculation, including capillary perfusion and density, were measured at admission (T0) and 4 h (T4) and 12 h (T12) after admission. Sublingual depth of focus (DOF) of the microcirculation was used to quantify the tissue edema. Results: Nine patients were recruited with a mean total body surface area of 36% ± 23%. By T12, a median of 4085 mL (interquartile range [IQR]: 3714–6756 mL) of crystalloids and 446 mL (IQR: 176–700 mL) of 20% albumin were administered. The DOF increased significantly after crystalloid administration (T4 vs. T0, mean difference [MD]=27.4 µm, 95% confidence interval [CI]: 3.4 to 50.9, P=0.040). Following albumin administration, DOF significantly decreased (T12 vs. T4, MD=−76.4 µm, 95% CI: −116.6 to −36.1, P=0.002). Total vessel density decreased significantly with crystalloid administration (T4 vs. T0, MD=−3.5 mm/mm2, 95% CI: −5.7 to −1.4, P=0.004) but increased after albumin administration (T12 vs. T4, MD=6.2 mm/mm2, 95% CI: 3.2 to 9.3, P=0.001). Conclusion: Sublingual microcirculation measurement of DOF and other parameters provide a valuable tool for the assessment of tissue perfusion and edema in patients with severe burns. Further investigation is required to evaluate the role of albumin in increasing microcirculatory convection and reducing tissue edema.